2002
DOI: 10.1021/cm0212156
|View full text |Cite
|
Sign up to set email alerts
|

Organic−Inorganic Hybrid Structure of Calcite Crystalline Assemblies Grown in a Gelatin Hydrogel Matrix:  Relevance to Biomineralization

Abstract: Calcite particles are grown in a collagenous matrix using a counter-diffusion arrangement. Although microstructural analysis revealed a heterogeneous intergrowth of organic and inorganic phases within the particles, the composite growth is rather a consequence of local chemical environment that is not specific to the gelatin gel. However, using an artificial poly-acrylamide hydrogel results in a very different growth morphology. The addition of poly-aspartate to the pore solution in either gelatin or poly-acry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 16 publications
5
124
0
2
Order By: Relevance
“…Except for the phase transformation of vaterite to aragonite, the formation mechanism looks similar to the well-known fractal theory for the formation of spherical particles. The rod-dumbbell-sphere morphogenesis mechanism that was first proposed by Kniep et al [16,17] for the growth of fluoroapatite is also consistent with that reported by Löbmann et al [18] for calcite in gelatin gels instead of free solutions and by Yu et al [15,19] for BaCO 3 particles obtained by a mineralization reaction at room temperature in the presence of organic additives. It should be pointed out that whether the intrinsic electric field plays a role in directing the growth of needle-like aragonite is still unknown, and the roddumbbell-sphere morphogenesis mechanism still appears to be rather universal.…”
Section: Resultssupporting
confidence: 85%
“…Except for the phase transformation of vaterite to aragonite, the formation mechanism looks similar to the well-known fractal theory for the formation of spherical particles. The rod-dumbbell-sphere morphogenesis mechanism that was first proposed by Kniep et al [16,17] for the growth of fluoroapatite is also consistent with that reported by Löbmann et al [18] for calcite in gelatin gels instead of free solutions and by Yu et al [15,19] for BaCO 3 particles obtained by a mineralization reaction at room temperature in the presence of organic additives. It should be pointed out that whether the intrinsic electric field plays a role in directing the growth of needle-like aragonite is still unknown, and the roddumbbell-sphere morphogenesis mechanism still appears to be rather universal.…”
Section: Resultssupporting
confidence: 85%
“…This will affect local supersaturation and ultimately suppress or enhance nucleation as well as modify the resulting morphology. To further complicate matters, the appearance of the surfaces of aggregates has been found to vary as a function of position in the gel: particles formed closest to the Ca 2+ source showed rough surface terraces, characteristic of high supersaturation conditions, while those closest to the CO 3 2− source had smooth, faceted surface terraces, typical of lower supersaturation conditions [58]. The observation of multiple morphologies within the same gel matrix emphasizes the importance of fully understanding the role of growth conditions, and supersaturation, on the final structure although it is often difficult to determine the individual contributions of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…These include spindle-shaped, rhombohedrally truncated specimens obtained in the presence of malonic acid, [15] the development of additional (sometimes even structured) faces extending nearly parallel to the c-axis direction in the presence of g-carboxyglutamate or a-aminosuccinate, [16] malic acid together with urea, [17] glycoproteins extracted from sea-urchin spines, [18] and nacre proteins. [19] It is not clear at present whether the organic components under consideration and acting as growth modifiers are generally incorporated into the solid to form an inorganicorganic composite material, but some indications have already been reported with respect to incorporation of the organic component into the calcite host (sea-urchin proteins [20] as well as gelatine [21] ). More recent investigations deal with the incorporation of agarose gel fibers into porous calcite single crystals and the resulting (moderate) changes in morphology.…”
mentioning
confidence: 99%